2014
DOI: 10.1007/s10792-014-9968-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of traumatic cataract in adults at a reference center in Mexico City

Abstract: The purpose of the study was to determine the clinical presentation, mode of injury, surgical, and postoperative outcomes in adult patients with traumatic cataract. This is a clinical, observational, and retrospective study with review of records of patients in the period 2010-2012. Eighty patients were included, of whom 67 (83.75 %) were male. The mean age at presentation was 46 years (range 18-82 years). Sixty-four patients (80 %) had a closed-globe blunt ocular trauma and 16 (20 %) had an open-globe penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
9
2
Order By: Relevance
“…Shah et al reported that the average age was 27 years [6, 11] in India and Serna-Ojeda et al reported that it was 46 years in Mexico [16]. In our study, the ratio of males to females is about 2.1 : 1, different from other reports with ratio 3 : 1 [16, 17]. …”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Shah et al reported that the average age was 27 years [6, 11] in India and Serna-Ojeda et al reported that it was 46 years in Mexico [16]. In our study, the ratio of males to females is about 2.1 : 1, different from other reports with ratio 3 : 1 [16, 17]. …”
Section: Discussioncontrasting
confidence: 96%
“…In other researches, these percentages vary from 65.2% to 80% [6, 11, 16, 18, 19]. In our study, only 12.9% underwent phacoemulsification, which is much lower than the 96.3% reported by other researches [16].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Where capsular support is adequate, a three-piece IOL can also be positioned in the ciliary sulcus [43]. It has been shown; however, that improvement in visual acuity is statistically significantly higher when the IOL is placed in the bag compared to in the sulcus [44]. One explanation for this finding is those sulci IOLs incite a greater inflammatory response.…”
Section: Zonular Support and Iol Positioningmentioning
confidence: 99%
“…10 Policy decisions helpful in preventing this kind of trauma and improving the required trauma management services warrant an accurate estimate of the pattern of the ocular trauma in Indian population. 11 Most of our understanding of this issue is based on the studies from developed countries 12,13,14…”
Section: Introductionmentioning
confidence: 99%